The Impact of Television Drama in Understanding History - Adway, Abdallah (Journal of Al-Tamaddun, 2023)
Drama is an important source for knowing history in our time, as many historical series and films are produced. This study aims to explore the impact of dramatic treatment on historical texts in achieving understanding and memorizing scientific information presented to an audience. This study examines the manner in which elements of dramatic treatment such as dramatic structure, characters, accuracy of information, content, and location affect the effectiveness of historical TV drama, and further demonstrates the capacity of dramatic treatment in achieving this understanding. This study used a quantitative method by collecting quantifiable data, and used the questionnaire as a data collection tool. The population sampled consisted of West Bank Palestinians, who watched one of the most successful historical TV drama series, entitled Omar. Subsequently, data were subjected to statistical analysis by SPSS. This study concludes that the difficulties in understanding and memorizing scientific information are mitigated by learning information presented in the form of drama, which can enhance the audience’s comprehension and retention of information. Additional factors such as location and content contribute to the quality of understanding of historical drama presented through television, wherein if a drama producer seeks to effectively deliver historical information he or she must secure interest in content, which affects understanding by up to 34%, followed by location and décor, which affects it by up to 23%.